The fine tunning principle in the context of systems with deterministic chaos - Brus, Bartłomiej; Szydłowski, Marek (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2008)
From the beginning of the deterministic chaos research, the unpredictability has been its central theme. Interesting questions arise here: What are the consequences of chaos for the fine tuned processes? Are there fine tuning systems in reality? We investigate the possibility of defining a fine tuning parameter in terms of the Lyapunov principal exponent. We will critically evaluate the existing formulation of Hetesi and Vegh. We argue that such a quantification of a fine tuning parameter may be useful in the context of the debate between indifference and fine tuning principles for the Universe. We also propose how to define fine tuning evolutional paths of the Universe by using concepts of dynamical systems, namely the method of separatrices in the phase space.